THE STUDY OF SELF-DIRECTED CAREER DECISION MAKING DIFFICULTIES AND INFLUENCING FACTORS FOR SECONDARY SCHOOL STUDENTS - Briška, Linda; Dišlere, Vija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
In the current situation many Latvian secondary school students do not know what specialty to choose to study or what work to choose during the last month of school studies. The aim of the study is to find out self-directed career decision-making difficulties and its influencing factors for the secondary school students. The study was developed in the Latvia University of Agriculture, in the Institute of Education and Home Economics within the Master study programm Career Counsellor. 68 secondary school students were involved in the study from regional secondary schools of Latvia. The surveys were conducted in 2016 and 2017. The results of the study showed that secondary school students, adopting a career decision, has to overcome the difficulties: associated with low self-esteem level and pressure from others; social barriers; internal conflict, the fear of risk-taking, acceptance of responsibility and seriousness of the decision, as well as lack of self-knowledge, too large number of options and uncertainties about the profession and themselves. The factors influencing career decision-making for secondary school students mainly are: the undestanding of their ability, skills, interests, characteristics, value, resources and conditions, self-image, environmental conditions, genetic diversity, learning experience, the ability to reflect on their own life experiences and construct their lives, as well as knowledge of professions and areas of vocational practice. Results of the research could be used in the work of school career counselor's.